ASPECTS OF THE FORMATION OF INFORMATION COMPETENCE OF PRIMARY SCHOOL STUDENTS - Albina Venerovna Sadikova; To'lqinali Usmonovich Abdullayev; Alyona Aleksandrovna Volkova (Galaxy International Interdisciplinary Research Journal, 2022)
The article reveals aspects of the formation of information competence of younger students, the need to use information and communication technologies in teaching younger students. It is also proposed to introduce computer literacy lessons into the educational process. The role of information and communication technologies in optimizing the educational process and improving the quality of education in primary grades is considered.